2022
DOI: 10.3390/plants11060824
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Four Cropping Patterns of Lilium brownii on Rhizosphere Microbiome Structure and Replant Disease

Abstract: Replant disease caused by continuous cropping obstacles commonly occurs in a Lilium brownii consecutive monoculture. To reveal the mechanisms contributing to the continuous cropping obstacles of L. brownii, four cropping patterns (fallow, L. brownii-rice rotation, newly planted L. brownii, and 2-year L. brownii consecutive monoculture) were designed, and Illumina MiSeq (16S rDNA and ITS) was utilized to detect shifts in the microbial community in the rhizosphere. Our result showed that planting of L. brownii s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…Long‐term CC of vanilla has also been shown to considerably improve the fungal community in previous studies (Xiong et al, 2015), and the bacterial diversity decreased during tobacco CC in soil (Yan et al, 2021). Past studies also suggested that prolonged CC could improve fungus biomass and decrease bacteria biomass, while long‐term CC of ginger might increase bacterial diversity, form bacteriostatic soil and inhibit soil sickness (Ma, Liao, et al, 2022; Yu et al, 2022). CC of chrysanthemum also promoted the fungal growth, and inhibited beneficial soil bacteria (Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Long‐term CC of vanilla has also been shown to considerably improve the fungal community in previous studies (Xiong et al, 2015), and the bacterial diversity decreased during tobacco CC in soil (Yan et al, 2021). Past studies also suggested that prolonged CC could improve fungus biomass and decrease bacteria biomass, while long‐term CC of ginger might increase bacterial diversity, form bacteriostatic soil and inhibit soil sickness (Ma, Liao, et al, 2022; Yu et al, 2022). CC of chrysanthemum also promoted the fungal growth, and inhibited beneficial soil bacteria (Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, the monocropping of Chinese yam has caused serious soil-borne diseases, resulting in reduced yield or even no harvest, causing significant economic losses, which have seriously restricted the development of the Chinese yam industry. Based on previous reports, there are various factors contributing to the soil-borne diseases, including inappropriate farming operations, soil physicochemical property disorders, and the functional and structural imbalance of the soil microbial community [ 10 , 11 ]. Soil microorganisms are active in and vital for soil ecosystems and participate in transforming nutrients, such as decomposing organic matter, promoting nutrient cycling, and maintaining soil fertility [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous reports, there are various factors contributing to the soil-borne diseases, including inappropriate farming operations, soil physicochemical property disorders, and the functional and structural imbalance of the soil microbial community [ 10 , 11 ]. Soil microorganisms are active in and vital for soil ecosystems and participate in transforming nutrients, such as decomposing organic matter, promoting nutrient cycling, and maintaining soil fertility [ 11 ]. Rhizosphere is the area near plant roots, and the bacterial community in this region is important for plant growth and health [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…选择间作种植模式后, 土壤 养分含量、微生物活性以及微生态稳定性得到一定 改善 [10] . 作物多样性是构建持续、稳定、健康、高产 的农田生态系统的重要方式之一, 利用作物多样性来 减轻连作障碍、控制作物病害是目前国内外研究的 热点问题之一 [11] .…”
unclassified